2013
DOI: 10.1186/1129-2377-14-90
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and predictors of headache in patients referred to polysomnography

Abstract: BackgroundThe objectives of this study were; (1) to assess the prevalence and frequency of headache in patients referred to polysomnography (PSG) due to a clinical suspicion of obstructive sleep apnea (OSA) or another sleep disturbance and compare with a reference population, and (2) to assess the association of OSA severity with headache and headache frequency.MethodsA total of 784 participants filled in a headache questionnaire between 2003 and 2009 at the Department of Clinical Neurophysiology, Akershus Uni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…Sleep apnea headache should be excluded when evaluating a preexisting primary headache. 44,45 Adequate treatment of OSAS with chronic headache with CPAP and prophylactic drug therapy proved effective in headaches in 30% of patients with CM. Other authors such as Goksan et al 46 and Loh et al 47 demonstrated that 80–90% of morning headaches improved after appropriate treatment for OSAS.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sleep apnea headache should be excluded when evaluating a preexisting primary headache. 44,45 Adequate treatment of OSAS with chronic headache with CPAP and prophylactic drug therapy proved effective in headaches in 30% of patients with CM. Other authors such as Goksan et al 46 and Loh et al 47 demonstrated that 80–90% of morning headaches improved after appropriate treatment for OSAS.…”
Section: Resultsmentioning
confidence: 99%
“…Patients with OSAS-associated headaches appear to be more likely to respond to treatment with continuous positive airway pressure (CPAP), confirming its efficacy in headaches, which could differentiate other headaches that mimic sleep apnea headaches. [43][44][45][46] The frequency of morning headaches in participants with OSAS (11.8%) compared to those without OSAS (4.16%) in the general population. 40 Patients with CM and OSAS share common risk factors such as obesity, middle age, and snoring.…”
Section: Comorbidities To Prevent and Treat To Improve Quality Of Lifementioning
confidence: 99%
“…Patients with headache may have poor sleep quality, reduced total sleep time, more awakenings, and alterations in architecture of sleep recorded by polysomnography (PSG) [13]. Prevalance of chronic headache was found to be higher in patients who underwent polysomnographic investigation due to sleep problems [14].…”
Section: Introductionmentioning
confidence: 99%